Highly unsaturated fatty acid synthesis in marine fish: Cloning, functional characterization, and nutritional regulation of fatty acyl delta6 desaturase of Atlantic cod (Gadus morhua L.) - Tocher, Douglas R; Zheng, Xiaozhong; Schlechtriem, Christian; Hastings, Nicola; Dick, James R (Lipids, 2006)
Fish contain high levels of the n-3 highly unsaturated fatty acids (HUFA), eicosapentaenoic (EPA) and docosahexaenoic (DHA) acids that are crucial to the health of higher vertebrates. Biosynthesis of HUFA requires enzyme-mediated desaturation of fatty acids. Here we report cloning and functional characterisation of a ∆6 fatty acyl desaturase of Atlantic cod (Gadus morhua), and describe its tissue expression and nutritional regulation. PCR primers were designed based on the sequences of conserved motifs in available fish desaturases and used to isolate a cDNA fragment from liver of cod. The full-length cDNA was obtained by Rapid Amplification of cDNA Ends (RACE). The cDNA for the putative fatty acyl desaturase was shown to comprise 1980bp which included a 5’-UTR of 261bp and a 3’-UTR of 375bp. Sequencing revealed that the cDNA included an ORF of 1344 bp that specified a protein of 447 amino acids. The protein sequence included three histidine boxes, two transmembrane regions, and an N-terminal cytochrome b5 domain containing the haem-binding motif HPGG, all of which are characteristic of microsomal fatty acid desaturases. The cDNA displayed Δ6 desaturase activity in a heterologous yeast expression system. Quantitative real time PCR assay of gene expression in cod showed that the ∆6 desaturase gene, was highly expressed in brain, relatively highly expressed in liver, kidney, intestine, red muscle and gill, and expressed at much lower levels in white muscle, spleen and heart. In contrast, the abundance of a cod fatty acyl elongase transcript was high in brain and gill, with intermediate levels in kidney, spleen, intestine and heart, and relatively low expression in liver. The expression of the Δ6 desaturase gene and the PUFA elongase gene may be under a degree of nutritional regulation, with levels being marginally increased in livers and intestine of fish fed a vegetable oil blend by comparison with levels in fish fed fish oil. However, this was not reflected in increased Δ6 desaturase activity in hepatocytes or ...